Existence Results for Super-Liouville Equations on the Sphere via Bifurcation Theory (Journal of Mathematical Study, 2021)
We are concerned with super-Liouville equations on $\mathbb{S}^2$, which have variational structure with a strongly-indefinite functional. We prove the existence of nontrivial solutions by combining the use of Nehari manifolds, balancing conditions and bifurcation theory.
Keywords: Super-Liouville equations; existence results; bifurcation theory; critical groups.